The Liouville theorems for 3D stationary tropical climate model. (17th August 2021) - Ding, Huiting; Wu, Fan
Abstract : In this paper, we will consider the Liouville theorems for the 3D stationary tropical climate model in whole space. In particular, we will prove that there is only the trivial solution for the stationary tropical climate model under some integrable hypotheses. The obtained results generalize and improve the classical results for the stationary Navier‐Stokes equations and MHD equations in some sense.